Where one cannot speak, there one can dance: a comparative analysis of dance movement therapy and Processwork. Issue 4 (1st October 2016) - Vasičáková Očenášová, Zuzana
Abstract: The text aims to outline the basic comparison of the theoretical roots, concepts and frameworks, principles, attitudes, typical interventions, phases of development and scope of practical use of dance movement therapy (DMT) and process-oriented psychology (Processwork). The author proposes that mutual benefits and opportunities are at disposal for practitioners from both schools, including the primary and secondary process and 'edge work' in Processwork, as well as movement observing techniques, movement profile mapping and the 'dance-not-done' approach in DMT. The theme of communication channels and the theme of 'essence level' or spiritual experience as approached in both practices is discussed as well.